The Influence of Capital Expenditure, Corporate Hedging, and Good Corporate Governance on Firm Value in Oil and Gas Sub-Sector Mining Companies on the IDX Period 2018-2020 - Muhammad Rizal; Taufik Hidayat; Arif Wahyudi (CERED Indonesia Institute, 2022)
This study aims to analyze how the influence of Capital Expenditure, Corporate Hedging, and Good Corporate Governance on Firm Value. This research was conducted at Mining companies in the Oil and Gas Sub Sector on the Indonesian Stock Exchange. the method used in this study is quantitative with multiple regression analysis. The results of this study indicate that Capital Expenditure, Corporate Hedging, and Good Corporate Governance have a significant effect on Firm Value both partially and simultaneously. for further research it is expected to be able to develop this research by adding variables and expanding the scope of research.